α- Glucosidase Inhibitory and Antioxidant Activities of Moluccella aucheri (Boiss.) Scheen Extracts - Mina Doorandishan; Morteza Gholami; Hossein Mirkhani; Pouneh Ebrahimi; Amir Reza Jassbi (Fasa University of Medical Sciences, 2021)
Background & Objective: α-Glucosidase is one of the main enzymes in the intestinal absorption of carbohydrates. Inhibition of this enzyme can improve postprandial hyperglycemia in diabetic patients. Also, antioxidants can ameliorate diabetes complications resulted from oxidative stress. In this study α-glucosidase inhibition, antioxidant activity and total phenol content of different extracts and obtained fractions of Moluccella aucheri have been evaluated. Materials & Methods: The ethanol extract of aerial parts of M. aucheri was fractionated using liquid extraction method with petroleum ether, dichloromethane and ethyl acetate, respectively. The extracts and the resulting fractions of M. aucheri were tested against α-glucosidase enzyme from yeast using an in vitro colorimetric model at λ 405 nm. Antioxidant activity was assessed using two different methods, ferric reducing antioxidant power (FRAP) and the scavenging activity of DPPH radicals' methods. Results: The screening results indicated that the antioxidant activity and total phenolic content of the methanol extract were potentially higher than ethanol extract, while the ethanol extract inhibited α-glucosidase enzyme to a greater extent. Ethyl acetate fraction illustrated potentially the highest antioxidant activity and phenolic content, but its inhibition activity against α-glucosidase was placed after the petroleum ether fraction. Two previously isolated methoxy flavones; genkwanin, 5-hydroxyl-7, 4'-dimethoxyflavone inhibited the α-glucosidase enzyme strongly. Conclusion: Since the ethyl acetate extract has both considerable antioxidant activity and α-glucosidase inhibitory activity, it may be considered as a potential crude drug for diabetes.